KONSENTRASI ABU SEKAM PADI TERHADAP KUALITAS MINYAK KOPRA - Irwan Irwan; Nur Alam; Asrawaty Asrawaty (Jurnal Pengolahan Pangan, 2019)
This study aims to determine the effect of the concentration of the use of rice husk ash on the quality of copra oil and obtain the concentration of rice husk ash which has the best influence on the quality of copra oil. This research was carried out in the laboratory of Agro-Industry Faculty of Agriculture, University of Tadulako Palu. This study uses a Completely Randomized Design (CRD). The treatment that was tried was rice husk ash consisting of 6 concentration levels namely 0, 5, 10, 15, 20 and 25% (v / v). Each treatment was repeated 3 times so that there were 18 observation units. The parameters observed were oil recovery, water content, free fatty acid content and degree of oil clarity. The data obtained were analyzed by variance, when showing the effect continued with the BNJ test at the level of 5%. The results showed that the treatment of rice husk ash concentration had a very significant effect on recovery, moisture content, free fatty acid content and clarity of copra oil. the concentration of rice husk ash concentration of 20% gives a better influence on the quality of copra oil.